E-modules assisted learning: Mathematical reasoning of junior high school students in solving mathematical literacy problems - Nailis Safiro; Novita Sari; Zuli Nuraeni; Novika Sukmaningthias; M. Hasbi Ramadhan (Universitas Hamzanwadi, 2026)
The growing use of digital learning media in mathematics classrooms has not been matched by sufficient evidence of students’ mathematical reasoning (MR) when solving mathematical literacy problems. This study aims to analyze the MR of junior high school students at different MR levels while solving mathematical literacy problems on systems of linear equations in two variables (SLETV) in a learning context supported by a mathematical literacy-based e-module. Using a descriptive qualitative design, the study involved ninth-grade students from a public junior high school in Palembang, South Sumatra, Indonesia. Data were obtained through three written mathematical literacy problems and follow-up semi-structured interviews and then analyzed using three MR indicators: finding patterns of relationships and generalizing a statement, proposing conjecture, and verifying the truth of an argument. The results reveal that students’ MR remains limited, with only a small proportion demonstrating medium to high-level reasoning. High-reasoning students are already capable of demonstrating all indicators of MR, but low-reasoning students struggle to develop mathematical models from contextual problems. These findings suggest that e-module-assisted learning can support reasoning, but students at lower reasoning levels still require more explicit scaffolding, particularly for modeling, conjecturing, and justification.